Early Complications in Modified Radical Mastectomy and Level-II Axillary Clearance for Carcinoma Breast in a Tertiary Care Centre: A Retrospective Cross-Sectional Study (Journal of Society of Surgeons of Nepal, 2025)
Introduction: Breast carcinoma is the most common cancer in woman and is the second common mortality in woman globally. There are different treatment modalities for breast cancer. The Modified Radical Mastectomy with axillary clearance is one important surgical treatment of carcinoma breast. The main aim of this study is to determine early complications after MRM and axillary clearance in carcinoma breast. Methods: This is a retrospective cross-sectional study conducted in department of Surgery, Patan Hospital, Patan Academy of Health Sciences from March 2022 to February 2025. This study included all patients undergoing MRM with axillary clearance and excluded patients undergoing toilet mastectomy and breast conserving surgery. Results: This study included 37 patients and the mean age was 53.78 ±11.89 years. Early complications were noted in 11 patients (29.73%), among which seroma was found in 4 patients (10.81%), followed by margin necrosis in 3 patients (8.1%), flap necrosis in 2 patients (5.4%), wound infection in 1 patient (2.7%) and hematoma in 1 patient (2.7%).Conclusion:  In our study seroma formation was the most common early complication in MRM with level II axillary clearance followed by margin necrosis, flap necrosis, wound infection and hematoma formation respectively.